Clusters - a Way to Economic Development in Central and Eastern European Countries - Pohulak-Żiołędowska, Elżibieta (Ekonomika, 2008)
Clusters can be localized in almost every economy. Criteria used during cluster mapping allow to localize concentrated enterprises and other entities which might created a cluster. It is helpful in fostering clusterbased economic development. Europe tends to rank high on the quality of institutions, but low on its ability to mobilize these inputs through entrepreneurship and new firm formation. Europe also tends to rank high on R&D spending and scientific capacity but low on its ability to turn research into economically valuable innovations. Clusters have the potential to transform outcomes in both dimensions: healthy clusters provide an accessible network of skills and capabilities, i.e. a microeconomic business and innovation environment that enable entrepreneurs to move from an idea to a business activity. And healthy clusters provide an efficient environment to move from a scientific advance or a new business concept to a market test. Central and Eastern Europe on countries are a special region with the planned economy in their history. Clusters might be a good solution for their problems, they can be “engines” of the economy if they grow in the right environment. But we mustn’t expect that the second Silicone Valley appears in our neighbourhood. Clusters develop over time, and clusters in Central and Eastern European countries are still labourintensive, not technologyintensive ones. And a unique history of the region, which is part of its path of development, determines its future. So, the question “Are clusters a right way of economic development for the CEEC?” deserves a positive answer. But it is worth noting that the unique conditions create unique solutions, so clusters - yes, but different than in Western Europe and probably never that effective.